TahlÄ«l MuhtawÄ wa MustawÄ As'ilat IkhtibÄrÄt Al-Lughah Al â€˜Arabiyah Li ImtihÄn Al Madrasah 'alÄ al Ma'ÄyÄ«r Al Wathaniyyah 'alÄ IthÄr Al Manhaj 2013 - Muhammad Natsir (Arabic Education Program IAIN Pekalongan, 2020)
Abstract The 2013 curriculum demands a paradigm shift in learning, process, and evaluation, including in HOTS, MOTS, LOTS-based assessments. Using an evaluative research design, this study aims to analyze the Arabic language test items in the UAMBN Madrasah Aliyah under LP. Ma'arif Kabupaten Jepara for the Academic Year 2018/2019. The analysis includes the design and approach used in preparing the test, the content (materials) of the test, and the categorization of the quality level of the test items in the 2013 Curriculum, i.e. HOTS, MOTS, or LOTS. The results showed that: first, the approach used in preparing the test was an integrative approach for multiple-choice test questions and a discrete-point test approach for essay test questions. Second, the content of the test included Arab and Indonesian culture and civilization, Muslim figures, language level, language rules, and sentence structure. Third, Arabic language test questions in UAMBN covered HOTS, MOTS, and LOTS questions. In the multiple-choice questions, 11 questions (27.5%) were included in the LOTS category, 10 questions (25%) in the MOTS category, and 19 questions (47.5%) in the HOTS category. Meanwhile, the essay questions, which presented 4 questions (80%) for the HOTS category and 1 question (20%) for the MOTS category, were considered less proportional. Overall, the format for the Arabic test in the UAMBN Madrasah Aliyah has been proportional because it has accommodated questions with the HOTS, MOTS, and LOTS categories.